β-glucan administration induces metabolic changes and differential survival rates after bacterial or viral infection in turbot (Scophthalmus maximus) - Librán-Pérez, Marta; Costa, M. M.; Figueras Huerta, Antonio; Novoa, Beatriz (Fish & Shellfish Immunology, 2018)
10 pages, 6 figures The innate immune response is able to ward off pathogens and remember previous infections using different mechanisms; this kind of immune reaction has been called “trained immunity”. Changes in cellular metabolism (aerobic glycolysis) have been observed during training with some immunostimulants like β-glucans or during viral and bacterial infections. We hypothesize that β-glucans can induce metabolic changes used by the host to fight pathogens. Accordingly, we evaluated changes in metabolic parameters in turbot that could affect their survival after a previous intraperitoneal treatment with β-glucans and subsequent administration of Viral Hemorrhagic Septicemia Virus (VHSV) or bacteria (Aeromonas salmonicida subsp. salmonicida). The results obtained support that β-glucans, VHSV and A. salmonicida induce changes in lactate, glucose and ATP levels in plasma, head kidney and liver and in the mRNA expression of enzymes related to glucose and fatty acid metabolism in head kidney. Additionally, the metabolic changes induced by β-glucans are beneficial for VHSV replication, but they are harmful to A. salmonicida, resulting in reduced mortality. β-glucans appear to have great therapeutic potential and can induce trained immunity against bacterial disease but not against viral disease, which seems to take advantage of β-glucan metabolic alterations This work was funded by the projects AGL2014-51773-C3 and BIO2017-82851-C3-1-R from the Spanish Ministerio de Economía y Competitividad, Proyecto Intramural Especial, PIE 201230E057 from Agencia Estatal Consejo Superior de Investigaciones Científicas (CSIC) and IN607B 2016/12 from Consellería de Economía, Emprego e Industria (GAIN), Xunta de Galicia. M.L-P was the recipient of postdoctoral fellowships from the Ministerio de Economía, Industria y Competitividad (FJCI-2015-24106) Peer reviewed